1998
DOI: 10.3109/10611869808996834
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Rate in Normal and Tumor-bearing Rats in Conscious State, under Urethane Anesthesia, and during Systemic Hypothermia

Abstract: The blood flow rates of 14 tissues in the body were determined by microsphere method using normal and tumor-bearing rats kept conscious or under urethane anesthesia. The effects on the blood flow rate in the tissues were assessed for multimodal therapy, systemic hypothermia for ischemic brain injury, and local hyperthermia and angiotensin II-induced hypertensive chemotherapy for cancer. Urethane anesthesia showed no effect on cardiac output, while there was a tendency of decrease of blood flow rate and % of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…It has been reported that the levels of endogeneous reducing agents such as thiols and ascorbic acid, which can rapidly reduce the nitroxide, are increased in gastric cancer (40,41). It has also been reported that the blood flow of tumors such as carcinosarcoma can be lower than that in the normal stomach (42). When the infusion rate is low in the endogenous reducing agent-rich tissue, the amount of delivered nitroxide and its contact time with the endogenous reducing agent would be increased, resulting in an increase in the amount of the reduced nitroxide.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the levels of endogeneous reducing agents such as thiols and ascorbic acid, which can rapidly reduce the nitroxide, are increased in gastric cancer (40,41). It has also been reported that the blood flow of tumors such as carcinosarcoma can be lower than that in the normal stomach (42). When the infusion rate is low in the endogenous reducing agent-rich tissue, the amount of delivered nitroxide and its contact time with the endogenous reducing agent would be increased, resulting in an increase in the amount of the reduced nitroxide.…”
Section: Discussionmentioning
confidence: 99%
“…A blood‐flow limited hybrid PB‐PK model was used to simulate gallamine concentrations in MIF using the following equation: where V MIF is muscle interstitial fluid volume, C A is gallamine arterial plasma concentrations, Q M is muscle blood flow, K p is MIF–plasma partition coefficient, and C MIF is gallamine MIF concentrations. In this simulation, estimates of V MIF and Q M of urethane‐anesthetized rats were obtained from the literature 20,21 . V MIF is approximately 11% of muscle tissue and the percentage of muscle tissue is approximately 50% of the total body weight 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, metformin flux through the portal vein (Q gl ) was calculated as the sum of systemically derived amounts, drug amounts infused in the portal vein (in the case of intraportal infusion), and transfer of metformin from GI wall to liver compartment that was derived from the absorption from GI lumen (for intraduodenal bolus and infusion). Systemically derived drug amounts in the portal vein were calculated as metformin plasma concentrations multiplied by portal blood flow (5.92 Ïź 0.97 ml/min/100 g body weight; Sakaeda et al, 1998).…”
Section: Stepensky Et Almentioning
confidence: 99%